(untitled) (CIPEEX, 2025)
Financial technology (fintech) plays an important role in improving the socioeconomic conditions of countries, while banking institutions have their digital transformation driven by this same technology. In addition, the aim is to analyze how the banking sector has reacted to the impact of financial technology on its services. This study consists of an integrative review of a qualitative nature, carried out by searching the Scopus and Web of Science databases. Descriptors organized into three keyword blocks were used, referring to the following terms: "physical bank", "digital banking" and "banking technology", combined with Boolean operators AND and OR. The inclusion criteria used were studies published between 2022 and 2024, available in English, and articles. Studies whose keywords were not aligned with the proposed theme, articles that were not freely accessible and duplicates were excluded. In this context, one of the pioneering sectors to deal with digitization was banking, and the pandemic has further boosted this process. In this way, technology, together with science on a global scale, is changing companies, making them more competitive and favorable to sustainability. On the other hand, financial technology has progressed very quickly, leading to the disappearance of conventional banks as a result of financial institutions stealing from their users. However, banking institutions that effectively implement digital modernization are able to better meet customer needs and provide a better service experience, taking into account crucial elements such as continuous innovation, the generation of trust, clarity on the part of the provider and clear communication of the benefits. Thus, fintech is related to better service and is perceived as a stimulus for bank customers to choose to migrate from their current bank to a digital bank. In addition, when choosing a bank, reliability is considered the essential requirement, followed by ease of use of services. In addition, the volume of user data accessible for banks’ digital modernization strategies has grown due to the propensity of these individuals to employ card swipe transactions at compatible payment terminals and digital services. This impetus has led the banking sector to commit itself to protecting the personal data, and their employees are on the front line, worrying as much about communicating their efforts not to lose the customer’s trust as about protecting their data. Therefore, the digital transformation driven by financial technology is redefining banking services, with significant changes during the pandemic. This evolution aims not only to improve the efficiency of services, but also to guarantee the security of customer data.